Alterações ante mortem e pseudopatologias em exoesqueleto de cingulados pleistocênicos de grande porte da região intertropical brasileira - Lima, Fábio Cunha Guimarães de (Universidade Federal Rural do Semi-Árido, 2017)
The order Cingulata is one of the most representative members of the Pleistocene Brazilian Megafauna. It is composed by well-known animals (armadillos, pampatheres and glyptodonts) and characterized by a peculiar bony exoesqueleton. Several studies in paleoecology of cingulates involve this peculiar structure, whatever, few studies have directed their attention to pathological alterations in the exoskeleton, despite its great potential in terms of paleobiological information. The aim of this work was to describe and identify exoskeletal diseases in large cingulates from the Pleistocene of the Brazilian Intertropical Region, providing new paleoecological insights for such animals. We analyzed exoskeletal elements collected in six localities of the Brazilian Intertropical Region deposited in three relevant fossil collections in the states of Minas Gerais, Pernambuco and Rio Grande do Norte. Through macroscopic examination, we have detected pathological and pseudopathological alterations affecting the surface of components of the exoskeleton in specimens of Hoplophorus euphractus, Panochuthus sp., Glyptotherium sp. and Pachyarmatherium brasiliense. These lesions included traumatic and infectious alterations generated by parasites in different parts of exoskeleton and the first records of lesions caused by fleas in glypdonts and in a large non-glyptodontid cingulate (Pachyarmatherium). Finally, we verified the presence of pseudopathologies, which served as a base for we propose a protocol to differentiate pathological to taphonomical alterations
Ante mortem alterations and pseudopathologies in exoskeleton of pleistocenic large body-mass cingulates from the brazilian intertropical region
Keywords: Região Intertropical Brasileira; Megafauna; Cingulata; Exoesqueleto; Paleopatologia; Brazilian Intertropical Region; Megafauna; Cingulata; Exoskeleton; Paleopathology; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA